Cadonilimab as second-line therapy in immunotherapy-resistant squamous NSCLC: a case report and review - Qiu, Shuo; Shi, Mingtao; Chen, Zhiying; Wang, Jing; Cui, Huanliang; Zhang, Yongchun (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have become a pivotal therapeutic option for the treatment of advanced non-small cell lung cancer (NSCLC), particularly as a standard first-line therapy. However, most patients eventually develop resistance to ICIs, and the options for second-line treatment remain limited with suboptimal efficacy. Cadonilimab, a novel bispecific antibody targeting programmed death-1 (PD-1) and cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), has demonstrated promising antitumor activity with a manageable safety profile. Nevertheless, its clinical efficacy in patients who have developed resistance to prior immunotherapy remains largely unexplored. This report presents a case of an elderly patient with early-stage NSCLC who developed resistance following first-line immunotherapy. After receiving subsequent treatment with cadonilimab, the patient achieved a partial response (PR) at the third cycle. The patient experienced substantial clinical improvement, including marked relief from chest tightness and shortness of breath, as evidenced by a reduction in modified Medical Research Council (mMRC) dyspnea grade from 3 to 1. The quality of life improved significantly, as indicated by a rise in the Karnofsky Performance Status (KPS) score from 60 to 80. Progression-free survival (PFS) was extended to 17 months, and the patient continues to derive clinical benefit. No immune-related adverse events (irAEs) affecting daily life occurred throughout the entire course of therapy. These findings suggest that cadonilimab may serve as a promising subsequent-line therapeutic option for patients with immunotherapy resistance.